Unilateral uveitis, cataract and retinal detachment following low-voltage electrical injury - Duman, Rahmi (Burns Trauma, 2015)
A 39-year-old woman presented with a gradual worsening of vision in the right eye 1 month after a low-voltage household electrical injury. A slit-lamp examination showed non-granulomatous anterior uveitis with nuclear cataract and an ultrasound examination also showed total retinal detachment. In this letter, we present a rare complication of electrical injury demonstrated as unilateral uveitis, cataract and retinal detachment in a 39-year-old woman.